Consensus on the Diagnosis and Treatment of Vitiligo in China (2021 Revision)# - The Vitiligo Expert Group of the Dermatovenereology Professional Committee, Chinese Society of Integrated Chinese and Western Medicine; Tie-Chi Lei; Ai-E Xu; Tian-Wen Gao; Li He; Hua Gu; Ming Li; Tie-Nan Li; Chun-Ying Li; Tong Lin; Kuan-Hou Mu; Chai-Xia Tu; et al. (Wolters Kluwer Health, 2021)
Abstract. Vitiligo is a common depigmented skin disease that negatively affects the physical and mental health of patients. The 2018 version of the Vitiligo Treatment Consensus has been updated based on the research progress on vitiligo in the past 3 years in combination with the clinical experiences of experts. The newly revised points include maintenance therapy, early glucocorticoid intervention, and oral mini-pulsed glucocorticoid administration protocols. The prospect of using JAK inhibitors in the treatment of vitiligo is also discussed.